1998
DOI: 10.1021/jp980930t
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Bubble Dynamics and Quantitative Sonochemistry

Abstract: We model the collapse of a bubble by taking into account all the energy forms involved (i.e., mechanical, thermal, chemical, and radiative) and compare the calculated radical yields with sonochemical data in H2O. Water decomposition plays a critical role in the energy balance, but trails equilibrium even in bubbles collapsing at subsonic speeds. Integration of the equation of bubble motion coupled with a full chemical mechanism reveals that (1) terminal gas temperatures and Mach numbers M L increase in cooler … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
135
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(143 citation statements)
references
References 26 publications
8
135
0
Order By: Relevance
“…Models with unrealistically low accommodation coefficients a ϳ0.001, like that of Colussi et al (1998), on the other hand, could well be condensation limited.…”
Section: Dissipative Models Including Water Vapormentioning
confidence: 99%
“…Models with unrealistically low accommodation coefficients a ϳ0.001, like that of Colussi et al (1998), on the other hand, could well be condensation limited.…”
Section: Dissipative Models Including Water Vapormentioning
confidence: 99%
“…At the interface [r ¼ R(t)], mass transfer is neglected, limiting the strict model applicability to forcing pressure wave frequencies above 100 kHz, where RP models have shown that the bubble dynamics is unaffected by evaporation/condensation. [26][27][28][29] Viscous stresses and radiation heat transfer are also neglected. Continuity, momentum, and energy transport equations applied to an infinitesimal shell about the interface yield the following relations, coupling bubble and liquid variables,…”
Section: Proposed Modelmentioning
confidence: 99%
“…We assume that in sonochemistry applications, the cavitation is transient and the bubble breaks apart at the collapse, dispersing the chemical contents into the liquid (S&S; Colussi et al 1998). Therefore, we are only interested in the rst expansion and violent collapse, a typical example is shown in gure 1.…”
Section: (G) Summarymentioning
confidence: 99%